2022
DOI: 10.1007/s00586-021-07053-2
|View full text |Cite
|
Sign up to set email alerts
|

Different degeneration patterns of paraspinal muscles in degenerative lumbar diseases: a MRI analysis of 154 patients

Abstract: Study design A retrospective study. Objective To evaluate the different degeneration patterns of paraspinal muscles in degenerative lumbar diseases and their correlation with lumbar spine degeneration severity. Summary of background data The degeneration characteristics of different paraspinal muscles in degenerative lumbar diseases remain unclear. Methods 78 patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Additionally, this phenomenon may be related to inserting the multifidus into the sacrum across multiple vertebral segments behind the lumbar spine alignment. 31 Furthermore, in the case of bending and torsion, we also found a similar situation: the model preserving the proximal MLC is relatively close to the normal physiological state. In extension, there is a situation beyond our conventional comprehension: Model C, which has more damaged posterior structures, shows more physiological ROM and maximum intradiscal stress.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, this phenomenon may be related to inserting the multifidus into the sacrum across multiple vertebral segments behind the lumbar spine alignment. 31 Furthermore, in the case of bending and torsion, we also found a similar situation: the model preserving the proximal MLC is relatively close to the normal physiological state. In extension, there is a situation beyond our conventional comprehension: Model C, which has more damaged posterior structures, shows more physiological ROM and maximum intradiscal stress.…”
Section: Discussionsupporting
confidence: 74%
“…3,4,28 Atrophy of damaged multifidus and fat infiltration after surgery occur, and clinical retrospective studies have shown that it may be related to ASD, especially the multifidus of adjacent segments. 7,[29][30][31] The multifidus is the core muscle group closest to the central axis of the spine; in addition to performing extension activities, its role is more reflected in strengthening the physiological lordosis sagittal alignment of the lumbar segment and acting as a dynamic stabilizer against flexion and torsion. 32,33 The PLC is an important part of the posterior column of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focus on the multifidus muscle in particular, given its role as a primary spine stabilizer [4]. The association between such degenerative changes in the multifidus muscle and poor patient outcomes highlights the clinical relevance in understanding the molecular drivers of these muscle changes [5][6][7]. Recent literature highlights the potential clinical impact of paraspinal muscle degeneration, as seen in studies concluding a higher risk of post-operative proximal junctional kyphosis, cage subsidence, and overall worse clinical outcomes in patients with lower paraspinal muscle volume and cross-sectional area [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…With the aging of the population, the incidence of lumbar degenerative diseases is gradually increasing. Recently, many studies focused on the degeneration of paraspinal muscle in lumbar degenerative diseases (1)(2)(3)(4)(5)(6), because paraspinal muscle plays an important role in maintaining stability. Ogon studied the degeneration of paraspinal muscles in 40 pairs of patients with chronic nonspecific low back pain and lumbar spinal stenosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Ogon studied the degeneration of paraspinal muscles in 40 pairs of patients with chronic nonspecific low back pain and lumbar spinal stenosis ( 7 ). Other studies also investigated the degeneration of paraspinal muscle in patients with low back pain ( 8 , 9 ) and lumbar degenerative kyphosis ( 3 , 10 ).…”
Section: Introductionmentioning
confidence: 99%